SÔBRE OS FLEBÓTOMOS DO TERRITÓRIO DO AMAPÁ, BRASIL - Forattini, Oswaldo P. (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1959)
The author gives the results obtained in Pll/ehotomus collections made at some localities o f the A mapa Territory, Brazil in decemher 1958 to april 1959. As more common species werc found P. amazonensis Root, P. squamiventris Lutz and Neiva, P. davisi Root, P. yleplliletor Fairchild and Hertig and P. paraensis Costa Lima. Nevertheless, there are some evidences ahout the importancc of P. squamiventris in local transmission of cutaneous leishmaniasis.